Introducing a data availability policy for journals at IOP Publishing: Measuring the impact on authors and editorial teams. Issue 4 (6th May 2021) - Holt, Jade; Walker, Andrew; Jones, Phill
Abstract: As the open research movement continues to gather pace, a number of publishers, funders, and institutions are mandating the sharing of underlying research data. At the same time, concerns about introducing extra quality control steps around data availability statements (DAS) are driving a discussion about the best way to make data more open without slowing down publication. This article describes a pilot project to introduce a new Open Data policy to three IOP Publishing (IOPP) journals as part of IOPP's commitment to increasing transparency and support for open science. An investigation was undertaken using an automated workflow monitoring tool to understand the impact of this change on authors and the editorial staff. Changes in revised submission processing times and how often manuscripts were returned to the author were measured. An overall increase in the time editorial staff spent processing manuscripts was found as well as an increase in the number of times manuscripts were returned to authors. Detailed analysis shows that manuscripts in which authors claim in the DAS to have included data within the manuscript were the most strongly affected. Steps to mitigate the effects through improved author communication were found to be effective.